2015
DOI: 10.1186/s13568-015-0125-4
|View full text |Cite
|
Sign up to set email alerts
|

Indole trimers with antibacterial activity against Gram-positive organisms produced using combinatorial biocatalysis

Abstract: The I100V isoform of toluene-4-monooxygenase was used to catalyze the oxidative polymerization of anthranil and various indoles under mildly acidic conditions, favoring the production of trimers. Compounds produced in sufficient yield were purified and tested for their ability to inhibit the growth of B. anthracis, E. faecalis, L. monocytogenes, S. aureus, and in some cases, F. tularensis. 15 of the compounds displayed promising antibacterial activity (MIC < 5 µg/ml) against one or more of the strains tested, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…There are reports in the literature of use of aromatic monooxygenases to produce tricyclic aromatic compounds as a result of addition reactions between oxygenate monoaromatic products (McClay et al. 2015 ), but to our knowledge the situation across the SDIMOs as a whole is the same as that obtained here, that oxygenation of triaromatic substrates has yet to be achieved and may reflect the size limitation of the active site across the wild-type enzymes of the class. Here, we have shown that the highly versatile sMMO can be engineered to alter the regioselectivty with aromatic substrates, including more precise hydroxylation of biphenyl at the 4-position, and we have achieved what to our knowledge is the highest specific activity (0.37 nmol min −1 mg −1 ) towards so large a substrate by cells expressing this group of enzymes.…”
Section: Discussionmentioning
confidence: 52%
“…There are reports in the literature of use of aromatic monooxygenases to produce tricyclic aromatic compounds as a result of addition reactions between oxygenate monoaromatic products (McClay et al. 2015 ), but to our knowledge the situation across the SDIMOs as a whole is the same as that obtained here, that oxygenation of triaromatic substrates has yet to be achieved and may reflect the size limitation of the active site across the wild-type enzymes of the class. Here, we have shown that the highly versatile sMMO can be engineered to alter the regioselectivty with aromatic substrates, including more precise hydroxylation of biphenyl at the 4-position, and we have achieved what to our knowledge is the highest specific activity (0.37 nmol min −1 mg −1 ) towards so large a substrate by cells expressing this group of enzymes.…”
Section: Discussionmentioning
confidence: 52%
“…7 They possess antiviral bioactivities and show activity towards other infectious illnesses such as hepatitis, mumps, pneumonia, and influenza. 8 They are also identified as potential drugs for the therapeutic targets of SARS-CoV-2 using a computational technique. 9 Because of the diverse applications of the indolinone framework, a number of approaches for their synthesis have been established.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, they are manufactured in the laboratory involving free radical pathways or metal-catalyzed, oxidant-driven, non-free radical approaches. [7][8][9][10][11][12][13][14][15] Bio-catalytically they are also synthesized from indoles using laccase catalysis, laccase-surfactant catalysis, biocatalytic process, and combinatorial biocatalytic approaches. 8,16,17 Likewise, these indolinone derivatives have been synthesized from indoles using a variety of reagents and conditions via some metal-free or metal-catalyzed routes.…”
Section: Introductionmentioning
confidence: 99%
“…Indazoles are an important class of bicyclic nitrogencontaining aromatic heterocycles and have attracted a great deal of attention in the past as well as in recent years due to their wide variety of biological properties. The indazoles represent an important subunit in drugs with a broad range of biological activities including antibacterial [1], antifungal [2], antiviral [3], antihypertensive [4], anticancer [5], anti-inflammatory [6], and immunomodulatory [7]. Indazoles with pyridine substituted compounds also have anti-cancer properties [8].…”
Section: Introductionmentioning
confidence: 99%